2017
DOI: 10.1093/mmy/myx026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Cryptococcus neoformans isolated from the environment in Beijing, China

Abstract: The molecular type of environmental Cryptococcus neoformans in Beijing was not clear. Our study aims to reveal the molecular characterization of C. neoformans complex from environment in Beijing, China. A total of 435 samples of pigeon droppings from 11 different homes in Beijing were collected from August to November in 2015. Pigeon droppings were inoculated onto caffeic acid cornmeal agar (CACA) to screen C. neoformans complex. Bruker Biotyper matrix-assisted laser desorption/ionization time-of-flight mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…A recent environmental study in China revealed that ST5 prevalence in nature was low (6.2%); thereby, one must be highly susceptible to the causal microorganism to be infected. In contrast, ST31 was commonly found in China (66.7%) 27 , but rarely caused any diseases (only 1.3% among cryptococcosis in East Asian countries, data not shown). However, it is still unclear whether this high susceptibility is due to genetic background or other factors.…”
Section: Discussionmentioning
confidence: 85%
“…A recent environmental study in China revealed that ST5 prevalence in nature was low (6.2%); thereby, one must be highly susceptible to the causal microorganism to be infected. In contrast, ST31 was commonly found in China (66.7%) 27 , but rarely caused any diseases (only 1.3% among cryptococcosis in East Asian countries, data not shown). However, it is still unclear whether this high susceptibility is due to genetic background or other factors.…”
Section: Discussionmentioning
confidence: 85%
“…17,18 Multilocus sequence typing (MLST) epidemiological studies from East Asia have shown limited genetic diversity among the majority of environmental and clinical isolates. 13,19,20 Different geographical areas have distinct population structures, particularly in relation to the predominant sequence types. 17 Previous studies suggested that though in relatively close geographical proximity, the population structure of C. neoformans var.…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely that the high prevalence of ST5 infection observed in HIV-uninfected patients is explained by a significantly greater prevalence of the lineage in the environment since it causes only 35% of cases in HIV-infected patients within the same geographical area 9 . Furthermore, data from China suggest that ST5 strains are significantly less prevalent in the environment, making up only 5% of isolates recovered in a recent study 29 . We investigated the first hypothesis by comparing previously identified in vitro virulence-associated phenotypes, along with murine in vivo virulence and immune responses, between lineages.…”
Section: Discussionmentioning
confidence: 95%